Application of poly(epsilon-caprolactone) nanoparticles containing atrazine herbicide as an alternative technique to control weeds and reduce damage to the environment - Pereira, Anderson E. S.; Grillo, Renato; Mello, Nathalie F. S.; Rosa, Andre H. [UNESP]; Fraceto, Leonardo F. [UNESP] (Elsevier B.V., 2014)
Nanoparticles of poly(epsilon-caprolactone) containing the herbicide atrazine were prepared, characterized, and evaluated in terms of their herbicidal activity and genotoxicity. The stability of the nanoparticles was evaluated over a period of three months, considering the variables: size, polydispersion index, pH, and encapsulation efficiency. Tests on plants were performed with target (Brassica sp.) and non-target (Zea mays) organisms, and the nanoparticle formulations were shown to be effective for the control of the target species. Experiments using soil columns revealed that the use of nanoparticles reduced the mobility of atrazine in the soil. Application of the Allium cepa chromosome aberration assay demonstrated that the nanoparticle systems were able to reduce the genotoxicity of the herbicide. The formulations developed offer a useful means of controlling agricultural weeds, while at the same time reducing the risk of harm to the environment and human health. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Green nanotechnology; Polymeric nanoparticles; Herbicidal activity; Genotoxicity